Makna Rezeki dalam Ayat-Ayat Al-Qur'an (Kajian Tafsir Ibnu Katsir) - Zubaedah, Siti (ojs.unsiq.ac.id, 2022)
If humans understand well what the meaning of sustenance is, then they will live their lives with obedience and happiness, but on the contrary, it is feared that humans will fall into the wrong understanding which then has a bad impact on themselves. The author is interested in expressing the word sustenance in the verses of the Qur'an using the book of interpretation of the Qur'an al-Azim or better known as the book of Tafsir Ibn Kasir by Sheikh al-Imam al -Hafiz Abu al-Fida 'Imanuddin Isma'il bin Umar bin Kasir al-Quraish al-Dimasyq because Ibn Kasir's commentary is one of the most famous books of interpretation of bil ma'sur in writing his commentary has the method that is in accordance with what Ibn Kas says in his book